2019
DOI: 10.1021/acsomega.9b01116
|View full text |Cite
|
Sign up to set email alerts
|

Light Trapping-Mediated Room-Temperature Gas Sensing by Ordered ZnO Nano Structures Decorated with Plasmonic Au Nanoparticles

Abstract: An ordered array of 1D ZnO nanorods obtained by colloidal templating is shown to dramatically enhance the sensing response of NO x at room temperature by confining light and creating periodic structures. The sensitivity is measured for a concentration varying from 2 to 10 ppm (response 53% at 10 ppm) at room temperature under white light illumination with ≈225 nm hole diameter. In contrast, structures with ≈450 nm hole size show better sensing under (response 98% at 10 ppm) elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Then, the surface states induced by these defects lead to an absorption in a visible region [ 13 , 23 ]. The previous study revealed that the configuration and size of the ZnO NR play an important role in light scattering and trapping [ 42 , 43 ], so that the surface area related to the visible PL is ascribed from the surface states. Meanwhile, in our ZnO NRs fabricated on the graphene/Cu structure, there are no PL peaks observed in the visible wavelength except the UV region, indicating a highly crystalline ZnO NR structure.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the surface states induced by these defects lead to an absorption in a visible region [ 13 , 23 ]. The previous study revealed that the configuration and size of the ZnO NR play an important role in light scattering and trapping [ 42 , 43 ], so that the surface area related to the visible PL is ascribed from the surface states. Meanwhile, in our ZnO NRs fabricated on the graphene/Cu structure, there are no PL peaks observed in the visible wavelength except the UV region, indicating a highly crystalline ZnO NR structure.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the catalytic effect of noble metals, the concept of localized surface plasmon resonance (LSPR) was also utilized to develop high-performance gas sensors at RT [ 53 , 54 ]. The introduction of LSPR effect into noble metal/MOS hybrids greatly expands the research in photoactivated gas sensors.…”
Section: Photoactivated Metal Oxide Semiconductorsmentioning
confidence: 99%
“…A relatively small number of reports have been published on the visible light activated gas sensitive properties of nanocomposites containing plasmon metal nanoparticles [ 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 ]. As an example, we can cite the work [ 169 ], in which the sensor properties of the ZnO/Au nanocomposite to C 2 H 2 were investigated.…”
Section: Activation Of Gas Sensitivity Of Semiconductor Metal Oxides Under Visible Lightmentioning
confidence: 99%